A review of select neglected and underutilized species in Tanzania - Marimo, Pricilla; Otieno, Gloria (2025)
The review study provides an overview of select neglected and under-utilized crop species in Tanzania highlighting the history of domestication, conservation and use of the crops, their contribution to food security, nutrition and livelihoods and their potential to contribute to food systems transformation in terms of resilience, food and nutrition security and value chains.